Save genetic resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Genes from the wild: Using wild genetic resources for food and raw materials, by Robert and Christine Prescott-Allen, Earthscan, 1983 Price: £3.00/$5.50 Available from Earthscan 3 Endsleigh Street London, WC1 H ODD United Kingdom and from Earthscan 17